Direct cost of inpatient wound dressing in South West Nigeria: A cross-sectional study - Kolawole Damilare Ogundeji; Wilson Wezile Chitha (PLoS ONE, 2025)
Background Wound dressing is an integral part of wound care protocol. However, the cost of dressing changes with the associated wound aetiology has not been well studied. The study investigates the cost implications of wound dressing across wound aetiology among hospitalized patients. Methods The study followed a descriptive cross-sectional research design to determine the cost of dressing changes and the associated wound aetiology among hospitalized patients. Study sites included medical-surgical units in three selected hospitals in southwest Nigeria. The study was conducted between May to July 2021. One hundred and ninety patients were recruited for the study. The eligibility criteria focused on patients hospitalized for at least four weeks or about to be discharged. Data collection was via a researcher-administered questionnaire. Ethical approval was received from the university and each of the hospitals. Results The finding shows that 34.2% of the respondents had road traffic accidents, followed by cancers, 22.6%, and surgical wound infections, 16.8%. Most patients were involved in daily (41.6%) or alternate-day (38.4%) wound dressing. Over 50% of the respondents earn less than US$30 per month, 34.7% earn between US$30 – US$60, while only 3.2% earn more than US$ 120. Also, 55.7% require 1–5 moderate or significant dressing packs per week. 75% had wound care paid for by relatives. The average burn injuries cost of wound dressing per week is estimated to be $8.42, while falls ($5.31), occupational injuries ($3.77), gunshot injuries ($3.74), and road traffic accidents ($3.49). The average cost of hospitalization for burn injuries per week was estimated to be $22.35, while for falls, road traffic accidents, and surgical wound infections, was $19.58, $19.32, and $18.37, respectively. Conclusions The cost requirements for prosperous wound dressing place a high financial burden on hospitalized patients in Nigeria. There is a need to scale Nigeria’s health insurance database to include the low socioeconomic class.